Immunochemical demonstration of J chain: a marker of B-cell malignancy. Issue 8 (August 1979) - Isaacson, P
Abstract : Many B-cell lymphomas can be shown to contain cytoplasmic immunoglobulin which is characteristically monotypic with respect to light chains. In Hodgkin's disease, however, the Reed-Sternberg cells have been shown to contain both immunoglobulin light chains. This finding, which is also present in some other lymphomas, has been used as evidence both for and against a B-cell derivation of these cells. J chain is present in normal immunoblasts irrespective of the class of immunoglobulin being synthesised and, thus, should be present in tumour cells that synthesise cytoplasmic immunoglobulin. In a series of lymphomas, in which the cells could be shown to contain immunoglobulin, J chain was present only in those tumours exhibiting a monotypic light chain staining pattern. J chain was not present in Reed-Sternberg cells and other cells staining polytypically for light chains. Demonstration of J chain is thus a useful marker for B-cell lymphomas; its absence in Reed-Sternberg cells indicates that the immunoglobulin in these cells is not synthesised by them and cannot be used as evidence for their derivation from B-cells.